Das Fördergebiet und der Galway Gaeltacht Survey. Zum geistig-kultruellen Problem einer Entwicklungshilfe - Leister, Ingeborg (ERDKUNDE, 1972)
Ireland’s Western Seaboard has been a planning object for the last eighty years. Although names have changed, area and targets remained the same and still do so, namely the economic and demographic stabilization of a poorly endowed habitat that is good only for providing a ready excuse for failure. But an independent Ireland has further burdened the task with an emotional issue by identifying the problem region with the surviving areas of the Irish national language (Gaeltacht). A mix-up has thereby resulted in which one can aim at revitalizing a language by means of physical planning. Though Ireland has a growth point programme (development centres) and, somewhat in conflict, macro-planning regions, two planning reports can, nevertheless, deal with the Galway Gaeltacht in splendid isolation. Analytical data for both reports were provided by one survey but the Galway Gaeltacht Survey, produced by the Social Science Research Centre at Galway U.C., came up with planning proposals which recognised, at least in a negative way, the existence of not just a different language but with it as well a different way of life. Though Scotland does provide a ready parallel, this view is not in line with official Dublin thought which therefore needed a second report. The present paper maintains that development aid, in this particural case as well as in general, is primarily a cultural problem and should be recognised as such by the donors as members of the dominant industrial urban society. Where stabilization of both a Gaeltacht and a subsistence economy are aimed at, aid is doormed to failure unless first the areas of conflict with a non-industrial society are firmly established and secondly aid is devised so as to minimize twese and the potential loss of a different way of life.